Analyzing Distribution Network Options at Remingtin Medical Devices - Munson, Chuck (Charles Lee); Xia, Yusen; Wallace, Walter L. (Pearson, 2013)
This new supply chain management case study examines Remingtin Medical Devices' opportunities to modernize distribution, optimize inventory levels, reduce transportation costs, and operate more effectively in an intensely competitive industry. It illuminates unique distribution challenges associated with medical device manufacturers' long-standing relationships with hospitals and surgeons, as well as the impact of healthcare reform and regulation in pressuring profit margins. Focusing on realistic distribution issues and challenges throughout, it offers exceptional value to both students and practitioners. Authors: Yusen Xia and Walter L. Wallace, both from Georgia State University.